Friday

April 25, 2014

April 25, 2014

Posted by **Adam** on Friday, October 29, 2010 at 6:53pm.

ln(x+8)+ln(x–8)=0

Im not sure how to approach this one. I tried moving the ln(x-8) to the other side and solving for x and that did not work. I also tried putting everything as an exponent to e. please help! thanks

- Calculus -
**Damon**, Friday, October 29, 2010 at 6:57pmthat is ln of product

ln (x^2-64) = 0

e^ln anything = anything

so

x^2-64 = e^0 = 1

x^2 -65 = 0

x = +/- sqrt 65

but ln of negative is undefined

so

x = +sqrt(65)

**Related Questions**

Pre-Calculus - I need help solving this logarithmic equation: ln x + ln (x+3) = ...

calculus - Please help me? ln(x+1)-ln(x-2)=ln(5) 1. Solve equation by setting up...

exponential and logarithmic graphs question - hi, i desperately need help ...

Math differentiation - 1. y = x^x 2. y = (sin^2xtan^4x)/(x^2+1)^2 3. y = x^(1/x...

math - Use properties of logarithms to condense the logarithmic expression. ...

College Algebra - Problem: Use Common or Natural Logarithims to solve the ...

Math - Which equation is equivalent to 3 ln 2 – ln 4 + 5 ln x = ln 3 + 2 ln 5? ...

Math - Which equation is equivalent to 3 ln 2 – ln 4 + 5 ln x = ln 3 + 2 ln 5? ...

Math - ln x^2(x+1)/x+2 Write in terms of ln(x), ln(x+1), and ln(x+2) is the ...

Help, Math. - Solve: 3e2x + 2 = 50 a. ln 8 b. ln 0.25 c. ln 14 d. 0.5ln 16...